Gaps and barriers preventing sustained delivery of HPV vaccination in Kano, Kaduna, and Lagos states: An exploratory qualitative study - Chidozie Ezechukwu; Esther Oluwayemisi Ayandipo; Demilade Osoteku; Raihanah Ibrahim; Oluwafunmilayo Raheem; Amy Boldosser-Boesch; Sarah Birse; Elizabeth Weinstein; Justice Nonvignon; Goodness Hadley; Eric Aigbogun; Uchenna Igbokwe (PLoS ONE, 2026)
Background To lessen the burden of cervical cancer, Nigeria introduced the HPV vaccine to its national immunization program, but the program has faced operational and contextual problems during its early rollout. This study explored the systemic and community-level barriers affecting HPV vaccine delivery across selected Nigerian states. Method This exploratory qualitative study employed key informant interviews with policymakers, immunization officers, government agencies, community-based organizations, and implementing partners across three states: Kaduna, Kano, and Lagos, from April 2025 to October 2025. Data were thematically analyzed using NVivo, with emphasis on identifying factors influencing the sustainability of HPV vaccination. The analysis focused on key domains such as policy implementation, financing, service delivery, supply chain systems, human resources, data management, and demand generation. Result The study found that HPV vaccine implementation is hindered by limited state-level policy adaptation, reliance on donor funding, human resource shortages, supply chain weaknesses, data management gaps, and strong socio-cultural resistance driven by misinformation. These interconnected barriers reduce vaccine acceptance and disrupt service delivery. Conclusion The HPV vaccination program in Nigeria is constrained by systemic weaknesses and socio-cultural resistance. Addressing these challenges requires stronger state-level policy adaptation, sustainable financing, improved supply chain and data systems, and targeted community engagement to enhance acceptance and ensure effective service delivery.